(untitled) (Journal of Kidney Cancer, 2021)
Wilms’ tumor (WT) in adults is a rare neoplasm. Only a few reports are available in the literature. The tumor often masquerades as renal cell carcinoma (RCC). For accurate reporting, histopathological examination (HPE) plays a vital role in early diagnosis and prompt administration of multimodality treatment helps to improve the prognosis. We comprehensively analyzed five cases of adult WT presenting in the third to fifth decade with flank pain, hematuria, fever, and palpable lump. After complete clinical, biochemical, radiological, and HPE evaluation, tumor was staged and treatment was planned accordingly. Patients with low-stage WT were treated with open radical nephrectomy and chemotherapy. One of the patients diagnosed with inferior vena cava (IVC) thrombus apart from the above treatment also underwent IVC thrombectomy. Another young male presenting with distant metastasis (stage IV) and focal anaplasia on histology received preoperative chemotherapy and then planned for surgery. Unfortunately, the tumor being unresectable, second-line chemotherapy was given but he ultimately succumbed to death. All other patients are on regular follow-up and disease-free. Adult nephroblastoma is a rare clinical entity with hostile behavior. The presence of IVC thrombus is not a contraindication to surgery. Although the management strategy as per pediatric protocol by the inclusion of multimodality approach improves survival, still the overall prognosis in adults is dismal. There is a need for a standardized treatment protocol to encourage a homogenous approach for this rare disease and thereby improve survival.